Discussion of Heated Tobacco Products on Twitter Following IQOS’s Modified-Risk Tobacco Product Authorization and US Import Ban: Content Analysis - Kim, Minji; Vassey, Julia; Li, Dongmei; Galimov, Artur; Han, Eileen; Kirkpatrick, Matthew G; Stanton, Cassandra A; Ozga, Jenny E; Lee, Sarah; Unger, Jennifer B (Journal of medical Internet research, 2024)
Understanding public opinions about emerging tobacco products is important to inform future interventions and regulatory decisions. Heated tobacco products (HTPs) are an emerging tobacco product category promoted by the tobacco industry as a "better alternative" to combustible cigarettes. Philip Morris International's IQOS is leading the global HTP market and recently has been subject to important policy events, including the US Food and Drug Administration's (FDA) modified-risk tobacco product (MRTP) authorization (July 2020) and the US import ban (November 2021). Although limited in their legal implications outside the United States, these policy events have been quoted in global news outlets and Philip Morris International's promotional communications, showing how they may potentially impact global tobacco regulation. Given the impending return of IQOS to the US market, understanding how the policy events were received through social media discourse will provide valuable insights to inform global tobacco control policy. This study aims to examine HTP-related social media discourse around important policy events. We analyzed HTP-related posts on Twitter during the time period that included IQOS's MRTP authorization in the United States and the US import ban, examining personal testimonial, news/information, and direct marketing/retail tweets separately. We also examined how the tweets discussed health and policy. A total of 10,454 public English tweets (posted from June 2020 to December 2021) were collected using HTP-related keywords. We randomly sampled 2796 (26.7%) tweets and conducted a content analysis. We used pairwise co-occurrence analyses to evaluate connections across themes. Tweet volumes peaked around IQOS-related policy events. Among all tweets, personal testimonials were the most common (1613/2796, 57.7%), followed by news/information (862/2796, 30.8%) and direct marketing/retail (321/2796, 11%). Among personal testimonials, more tweets were positive (495/1613, 30.7%) than negative (372/1613, 23.1%), often comparing the health risks of HTPs with cigarettes (402/1613, 24.9%) or vaping products (252/1613, 15.6%). Approximately 10% (31/321) of the direct marketing/retail tweets promoted international delivery, suggesting cross-border promotion. More than a quarter of tweets (809/2796, 28.9%) discussed US and global policy, including misinterpretation about IQOS being a "safer" tobacco product after the US FDA's MRTP authorization. Neutral testimonials mentioning the IQOS brand (634/1613, 39.3%) and discussing policy (378/1613, 23.4%) showed the largest pairwise co-occurrence. Results suggest the need for careful communication about the meaning of MRTP authorizations and relative risks of tobacco products. Many tweets expressed HTP-favorable opinions referring to reduced health risks, even though the US FDA has denied marketing of the HTP with reduced risk claims. The popularity of social media as an information source with global reach poses unique challenges in health communication and health policies. While many countries restrict tobacco marketing via the web, our results suggest that retailers may circumvent such regulations by operating overseas.